Ultrasonography Classification of the American Thyroid Association for Predicting Malignancy in Thyroid Nodules >1cm with Indeterminate Cytology: A Prospective Study - Rocha, Tiara Grossi; Rosario, Pedro Weslley; Silva, Alexandre Lemos; Nunes, Maurício Buzelin; Silva, Tulio Henrique; de Oliveira, Pedro Henrique Lopes; Calsolari, Maria Regina (Hormone and Metabolic Research, 2018)
The objective of this prospective study was to evaluate the ultrasonography classification of the American Thyroid Association (ATA) for predicting malignancy in thyroid nodules >1 cm with indication for fine-needle aspiration (FNA) whose cytology was indeterminate. Additionally, the combination of the ATA classification with Doppler analysis was evaluated. All patients with thyroid nodules >1 cm were eligible. Each nodule was assigned to one of the ATA categories. Exclusively or predominantly intranodular vascularity was considered suspicious. One hundred and thirty-seven patients with 143 nodules underwent FNA and those with indeterminate cytology (Bethesda category III or IV) were selected. All patients were referred for surgery. Among the 143 nodules evaluated, 92 were benign, 33 were malignant, 13 were noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP), and 5 were tumors of uncertain malignant potential (TUMP). The rate of malignancy, including NIFTP and TUMP in this definition, was 80%, 42.8%, 13%, 10%, and 23% for nodules with a high suspicion, intermediate suspicion, low suspicion, very low suspicion, and undefined ultrasonographic pattern, respectively. Considering NIFPT and TUMP as benign, these rates were 72%, 22.4%, 4.3%, 0%, and 15.4%, respectively. The addition of Doppler analysis did not significantly improve the prediction of malignancy obtained with the ATA classification alone. The results of this prospective study show the usefulness of the ATA ultrasonographic classification for predicting malignancy specifically in thyroid nodules >1 cm with indeterminate cytology. The ATA category of the nodule should influence the decision for follow-up, molecular tests, or surgery.
Keywords: thyroid nodule; indeterminate cytology; ultrasonography; American Thyroid Association; Doppler; malignancy